THE CHALLENGES FACING CONTEMPORARY PUBLIC ADMINISTRATION IN ACHIEVING EFFICIENT MANAGEMENT - Luiz Fernando Ridolfi; Luana Regina Machado de Oliveira; Maria do Socorro Melo; Hermócrates Gomes Melo Júnior; Mayra Cassandra da Silva e Sá; Mariana Aguiar de Souza Valois; Carmen Mercedes Ferreira; Antônio Alves Ribeiro (Artefactum - revista de estudos interdisciplinares, 2026)
Contemporary public administration faces challenges stemming from the growing complexity of social demands, institutional and budgetary constraints, inequalities in access to public services, and the need to incorporate digital technologies into management processes. In this context, this article aims to analyze the main challenges that affect the efficiency of Brazilian public administration and to discuss prospects for modernization guided by managerial innovation, digital transformation, governance, transparency, and citizen participation. This is a qualitative study based on a literature review and an analysis of experiences related to the modernization of public management and the adoption of technologies applied to the public sector. The analysis shows that administrative efficiency does not depend exclusively on the incorporation of technologies, but rather on the interplay between institutional capacity, civil servant qualifications, organizational innovation, governance, transparency, and social participation. The results also indicate that digital transformation can enhance the agility and responsiveness of public services, although its effectiveness depends on overcoming barriers related to technological infrastructure, information security, data protection, organizational resistance, and digital inclusion. It can be concluded that an efficient public administration requires an integrated approach capable of reconciling technological innovation, state capacity, institutional accountability, and the creation of public value. This study contributes to the contemporary debate by systematizing the challenges and prospects for public management oriented toward efficiency, inclusion, and improving the quality of services provided to society.